The Mineral Industry Of Alabama (The National Institute for Occupational Safety and Health (NIOSH), 1995)
Alabama ranked 19th in the Nation in nonfuel mineral value1 in 1994, down from 18th in 1993, according to the U.S. Bureau of Mines. The estimated value for 1994 was $576 million, a 2.5% increase over that of 1993. This followed a 3.5% increase in 1993 over that of 1992. The State accounted for a little less than 2% of the U.S. total. Nonfuel mineral production in Alabama consisted entirely of industrial minerals; no metals were mined in the State. Bauxite materials mined in the State are a natural mixture of bauxitic clay and bauxite having very low iron oxide content and are primarily used to make refractory (high temperature resistant) products, rather than in the production of primary aluminum. In descending order of dollar value, the top four mineral commodities produced in Alabama were crushed stone, portland cement, lime, and construction sand and gravel. These commodities accounted for almost 88 % of the State's total non fuel mineral value, while crushed stone and portland cement together represented almost 65 % of the total. In estimated mineral production for 1994, Alabama remained first in common clays and first of only two States that produced bauxite; third in lime, kaolin clays, and fire clays; seventh in portland cement and salt; and was one of the top seven States that produce bentonite clays. The State dropped from third to fifth in masonry cement. Production of talc and pyrophyllite resumed in 1994. Compared with 1993, the value of crushed stone, lime, construction sand and gravel, common clays, kaolin clays, fire clays, bauxite, and talc and pyrophyllite increased. Decreases occurred in portland cement, masonry cement, industrial sand and gravel, and dimension stone.